Relationship between flight muscle dimorphism and wing morphometry in Triatoma infestans (Klug, 1834) (Hemiptera, Reduviidae, Triatominae) - Nattero, Julieta; Piccinali, Romina V.; Fiad, Federico G.; Cano, Florencia; Carbajal-de-la-Fuente, Ana Laura (Frontiers in Ecology and Evolution, 2023)
Triatoma infestans (Klug 1839), the primary vector of Chagas disease in southern South America, is reported as a dimorphic species for flight muscle development and presents a marked phenotypic plasticity in traits related to flight. In triatomines, studying the relationship between flight muscle development and wing variation is important, since it involves flight capacity and dispersion. Therefore, we examined the association between flight muscle dimorphism and morphological wing variation in T. infestans individuals. We hypothesized that if the underdeveloped flight muscle were associated with a decrease in wing developmental stability, canalization and morphological aspect of wings, and with a loss of wing modularity, then wing variation would be associated with flight muscle dimorphism. Wing size and shape were characterized using geometric morphometrics. Patterns of canalization, developmental instability and modularity were inferred from fluctuating asymmetry (FA) analysis of wing shape. Morphological aspects of wings were estimated using maximum wing length and wing area. The results showed that there are differences in wing shape but not in wing size among groups. Canalization and developmental stability were positively associated in individuals with muscle development and negatively associated in individuals with underdeveloped flight muscles. The covariance structure of variation among individuals was different between groups but not for FA, both for females and males. Modularity hypothesis related to the wing subdivision into two parts, a stiff part and a membranous one, showed significant association for the variation among individuals and FA variation in females with flight muscles. Wing aspect showed that females with flight muscles exhibited more elongated and thinner wings than those without flight muscles. The results obtained in this study reveal an association between flight muscle development and forewing variation in T. infestans. Females with flight muscles have certain differential characteristics in their wings that would be related to an enhanced flight performance.